Dynamics of financial stress and economic performance : insights and analysis from the world economy - Thimmaraya, Ramesh Babu; Venkateshwarlu, M., 1960- (Emerald Publishing Limited, 2018)
The financial stress of 2008 propelled the world into the most severe recession since the great depression. Despite the significant risk that it poses to the real economy, the complex interaction between financial stress and economic performance is not well understood due to the crucial gaps that remain in our understanding of this critical and dynamic relationship. Dynamics of Financial Stress and Economic Performance: Insights and Analysis from the World Economy attempts to understand the complex non-linear dynamics between financial system stress and economic performance on a global level. An analytical approach is taken to examine twelve major countries, and provide a detailed understanding of the crucial financial and economic issues faced in light of financial stress; including interest rate bottoms, inflation asymmetries, financial health of households, money supply bubbles, fiscal issues, trade dynamics, over leveraging of the financial markets, behaviour of housing prices, debt problems, potential for economic growth, or a complex combination of any of the above. This book will appeal to practitioners, students and researchers in fields such as financial economics, risk management and quantitative finance who wish to expand their knowledge of these crucial and complex dynamics. It is also an appealing read for those who are generally curious about business, banking, financial markets and macro-economic issues occurring on both an individual country and global level.